Irish Liberty, British Democracy : the Third Irish Home Rule Crisis, 1909-14 - Doherty, James (Book collections on Project MUSE., 2019)
"The crisis over the third Irish Home Rule Bill of 1913-14 is remembered as a dramatic political controversy that brought Ireland to the brink of civil war. It remains an intriguing episode for students of history, not least because the unexpected outbreak of the First World War left its denouement permanently in suspense. James Doherty demonstrates that the leadership of the Liberal Party was out-of-step with the impulses of popular Liberalism, which viewed Irish Home Rule as a major component of a drive to democratise a British constitution still heavily weighted in the aristocracy's favour. Offering a fresh clue to the demise of the British Liberal Party, Doherty argues that a progressive groundswell demanded Home Rule not just as a solution to the Irish problem, but as the crucial instrument for the advance of British democracy. Irish Liberty, British Democracy challenges some entrenched beliefs about the role of the crisis in cementing the partition of Ireland, arguing that despite, or perhaps because of the perils swirling in Ireland in the summer of 1914, the possibilities of a unionist capitulation were not exhausted when the outbreak of the First World War altered the course of Irish and world history"--